Using the incidence and impact of health conditions in guide dogs to investigate healthy ageing in working dogs - Caron-Lormier, Geoffrey; England, Gary C.W.; Green, Martin J.; Asher, Lucy (Elsevier, 2016)
This study aimed to use retirement data from working guide dogs to investigate healthy ageing in dogs and the demographic factors that influence ageing. Using a dataset of 7686 dogs spanning 20 years, dogs withdrawn for health reasons before they reached retirement were identified. Cases of retirement for old age, rather than for health reasons, were also recorded, as was the length of working life for all dogs. Specific health reasons were grouped into 14 different health categories. The influence of purebred or crossbreed, breed, and sex on the incidence of these health categories and the length of working life within each health category was considered. The majority (n = 6465/7686; 84%) of working guide dogs were able to function as guide dogs until they had worked for 8.5 years, when they retired. This working life might constitute a reference for the different breeds considered, with the exception of the German shepherd dog, which had a shorter working life. The most common reason for health withdrawals was musculoskeletal conditions (n = 387/1362; 28%), mostly arthritis. Skin conditions (mostly comprised of cases of atopic dermatitis) reduced working life most commonly (mean, approximately 5 years). Nervous sensory conditions (35% of which were cases of epilepsy) reduced working life by 3 years.